2020
DOI: 10.1155/2020/4520769
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators of Pharmaceutical Care in Palestinian Integrative Healthcare Facilities: Findings of a Qualitative Study among Stakeholders

Abstract: Background. Recently, there has been shifts from providing large volumes to providing higher quality of healthcare services. This qualitative exploratory study was conducted to explore the views of different stakeholders on activities and services that could serve as quality indicators of pharmaceutical care in Palestinian integrative healthcare facilities. Methods. A judgmental sampling technique was used to invite and recruit stakeholders for this study. Semistructured in-depth interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…The results could provide a guide to hospitals’ decision-makers in order to have under control the situation of the Algerian healthcare system [ 46 ] and for the other countries healthcare systems, because our findings are in consensus with the results of the other researchers [ 47 , 48 , 49 ]…”
Section: Discussionsupporting
confidence: 88%
“…The results could provide a guide to hospitals’ decision-makers in order to have under control the situation of the Algerian healthcare system [ 46 ] and for the other countries healthcare systems, because our findings are in consensus with the results of the other researchers [ 47 , 48 , 49 ]…”
Section: Discussionsupporting
confidence: 88%
“…This study was part of a larger study that was conducted to develop a consensus-based core inventory of KPIs to be used in capturing the impact of pharmaceutical care in healthcare facilities that employ integrative medicine paradigm [ 33 , 34 ]. The present study is being reported in compliance with the Conducting and REporting of Delphi Studies (CREDES) guidelines [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Activities performed and services provided by pharmacists while caring for patients admitted to or visiting healthcare facilities that employ integrative medicine that potentially can be used as KPIs were collected from the literature into an initial inventory [ 33 ]. The list of activities and services collected from the literature was supplemented by additional activities and services that were provided by 9 CAM practitioners, 8 pharmacists, 2 physicians, 2 nurses, and 1 risk/quality assurance manager who were interviewed using in-depth semistructured qualitative interviews [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-structured in-depth qualitative interviews were conducted with educators/academicians and professionals (5 educators/academicians, 3 pharmacists, and 3 physicians) to explore their views and opinions on the objectives and intended learning outcomes of the history of medicine and pharmacy course. The aim of these interviews was to obtain additional objectives and intended learning outcomes that might not be provided in the retrieved articles [12][13][14][15][16]. The interviews were transcribed verbatim and the transcripts were analyzed thematically [12].…”
Section: In-depth Interviewsmentioning
confidence: 99%